Spillover effects of transportation capital and provincial competitiveness on economic growth in Vietnam - Le, Nhung (Journal of International Economics and Management, 2023)
This study uses the spatial econometric model to evaluate the impact of transportation capital and provincial competitiveness on economic growth in Vietnam. Data from 63 provinces and cities in Vietnam were collected between 2010 and 2017. It is found that both direct and indirect effects of transportation capital are positive and statistically significant, and that the spillover effect is strong. The findings confirm the high efficiency of synchronous investments in the transport infrastructure. In addition, the study points to the necessity of improving labor quality, which is closely related to the services provided by the provincial government: general education, vocational training, and employment service growth.